TEACHING STYLES AND EDUCATIONAL PHILOSOPHIES OF SECONDARY SCHOOL TEACHERS IN KANO METROPOLIS, NIGERIA - Saheed Olanrewaju Jabbar (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2018)
The objective of the study was to examine the prevailing teaching style and educational philosophies of teachers in Kano metropolis, Nigeria, and to determine whether there was a relationship between the two variables. Descriptive survey research design was used in the conduct of the study. The population of the study consisted of a sample of 124 secondary school teachers in Kano metropolis. Robert Leahy Philosophic Inventory (1995) was adapted as data collection instrument. The data obtained were analyzed using percentage, mean, t-test and ANOVA. Findings of the study reveal that lecture method was the most frequently used teaching method by teachers while essentialism was the predominating educational philosophy of teachers. A moderate positive relationship exists between teachers' preferred teaching style and their educational philosophies but no statistically significant difference was found in the teaching styles of the male and female teachers in Kano Metropolis. Similarly, there was no significant difference in teachers' teaching styles with respect to their qualifications. Among other things, the study recommends continuous professional development of teachers through regular in-service training in order to equip them with modern and contemporary educational philosophies and teaching styles.